Novos sulfetos e sulfonas fluorescentes: síntese e estudo das propriedades fotofísicas - Araújo, Matias Monçalves (2012)
In this study, we performed the synthesis of new symmetrical vinyl sulfides 2-4 by Wittig-Horner reaction of aldehydes derived from diphenyl-, triphenylamine and carbazole with bis[(diphenylphosphinyl)methyl]sulfide 1. The products were obtained in good yields and diastereoselectivities using methodologies well known in our research group. Aiming at the synthesis of photoluminescent compounds, and having vinyl sulfides as precursors, we obtained the vinyl sulfones 5-7 through a simple oxidation step, in good yields and selectively for the E,E isomer. The photophysical properties of vinyl sulfides were interesting, with maximum emission bands observed at blue region of the spectrum, between 411 and 458 nm. Oxidation of sulfide to their respective sulfones, obtaining D-π-A-π-D structures, alters greatly the photoluminescent properties of these compounds. The maximum absorption and emission bands are shifted to the red, due to the processes of intramolecular charge transfer. The strong influence of the solvent polarity suggests the existence of a very polar excited state. The absorptivity coefficients also indicate that the main transitions occur between π-π* electrons, being strongly influenced by the long π-conjugated system existing in these compounds.